Advanced method for measuring asphalt viscosity: Rotational plate viscosity method and its application to asphalt construction temperature prediction. (27th September 2021) - Luo, Haoyuan; Huang, Xiaoming; Rongyan, Tian; Ding, Haibo; Huang, Jinhui; Wang, Dalin; Liu, Yuhao; Hong, Zhengqiang
Highlights: Novel rotational plate viscosity method was proposed for asphalt viscosity testing. The method can be set up and performed using existing DSR machine. The method provided reasonable construction temperatures for modified asphalt. The method was more efficient, programmable, and accurate than traditional methods. Abstract: The traditional method for determining mixing and compaction temperatures of asphalt binders, such as Brookfield viscosity test, often yields excessively high temperatures when used in many modified asphalts, and underestimates the temperature decreasing effect of the additives when used in warm-mixing asphalts. This study proposed a new viscosity measurement method, namely rotational plate viscosity (RPV) testing, to overcome these issues. The new method uses a Dynamic Shear Rheometer (DSR) with a 25-mm-diameter parallel plate geometry and a fixed shear rate 40 s −1 to measure the viscosity-temperature curve of modified asphalts, which minimizes the effect of the shear-thinning behavior. In addition, there are two main advantages of this new method. First, it can be carried out using an existing standard DSR machine typically used in most asphalt binder laboratories. Second, it can greatly improve the accuracy and efficiency of testing with sophisticated sensors and programmed settings.